The relationship between Chlamydia pneumoniae infection and TNF-α in cardiovascular disease patients - Nasser, Hadeel A.; Ismael, May Khaleel; Al. Halbosiy, Mohammed M. F. (Iraqi Journal of Science, 2018)
Over the last few years the role of microorganisms in the pathogenesis of atherosclerosis has been widely discussed. Advance in basic science have established a fundamental role for inflammation immediating all stages of cardiovascular diseases. Chlamydia pneumoniae activates immune cells to produce cytokines such us TNF-α that are important contributor to atherosclerosis. All blood samples were assayed for molecular detection of Chlamydia pneumoniae by using conventional polymerase chain reaction (PCR) relying on16SrRNAand the level of serum TNF-α measured by enzyme linked immunosorbent assay (ELISA).Seventy patients who suffering from CVD (angina, myocardial Infarction and atherosclerosis) aged between 33-86 years have been investigated and compared to twenty of apparently healthy individuals were studies as control group. Twenty six sample (37.14) %detected positive results for Chlamydia pneumoniae by PCR techniques in patient group, while all control group were negative, furthermore current study revealed a highly significant elevation (p<0.01) in the mean level of TNF-α in sera of patients with CVD compared to control group. Also there were considerable differences in the level of TNF-α between Chlamydia pneumoniae positive and negative within the patient group. The present study concludes there is a significant proportion among patients who infected with C. Pneumoniae and these bacteria play an essential role in the pathogenesis of CVD through stimulation of the inflammatory response.